Gambaran Disonansi Kognitif Pada Perempuan Dewasa Awal Yang Bertahan Dalam Hubungan Intimate Partner Violence (IPV) - Maritza, Endhitya Davina; Diah Sosialita, Tiara (CV RIFAINSTITUT, 2023)
This research aims to describe the cognitive dissonance experienced by early adult women victims of Intimate Partner Violence (IPV). Researcher wants to know more of acts and impacts of violence, forms of cognitive dissonance experienced, the effect of dissonance reduction on victims' decisions to stay in IPV relationships, and coping strategies used by victims. This research uses a qualitative research method with an intrinsic case study approach involving three informants in the age range of 21-23 years. The participant search technique uses a purposive technique. The process of collecting research data is done through interviews with the member checking credibility technique. The data analysis technique used is data driven analysis technique. The results showed that the victim felt cognitive dissonance, namely a discrepancy between cognition and violent behavior committed by a partner. Victims are motivated to make the relationship work, they tend to make excuses, and rationalize the violence experienced to reduce perceived cognitive dissonance. The fear of loss, the belief that the partner will change, and the love for the partner made them stay in the relationship. Coping strategies used by IPV victims are seeking support from friends or people around them and channeling emotions through hobbies or activities they enjoy.